Social work in funeral homes, a unique Chinese practice? - Huang, Yunxian; Tan, Weijia; Tsang, A. Ka Tat (My University, 2021)
Social workers were introduced to funeral homes in China amid the transition and expansion of both the funeral home industry and the social work profession and are proving to play a valuable, though under-researched role in serving not just clients but also communities and funeral home staff. Funeral home social work fills gaps in after-death care and mental health and is distinct from palliative, hospice, end-of-life, and bereavement social work. Based on the experiences of funeral homes that employ social workers, this article argues that this innovation may bring new ideas to bridge some of the service gaps in after-death care in China and globally. This article outlines the support that will be needed from funeral homes, social work service agencies, and educational and research institutes to facilitate further development of funeral home mental health and social services and to promote the professionalization of funeral home social workers in China.
Keywords: social work; funeral home; after-death care; mental health; social service